Pelatihan Membuat Rencana Bisnis Pada Remaja Karang Taruna Bocah Sawah Bekasi - Srisulistiowati, Dwi Budi; Rejeki, Sri (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
Youth is the backbone to develop productivity in the community. Youth is an important figure in every change, so that in youth development it is necessary to have realistic planning, directed and supports development. One of the criteria for measuring the progress of a country is to look at the degree of composition of entrepreneurship, especially that of youth. On this basis, this community service program focuses on youth development in terms of entrepreneurship. The activities carried out are in the form of training online to make business plans, which aim to make young people -especially at Karang Taruna Bocah Sawah RW 05 Kavling Sawah Indah Bekasi - able to understand and understand how to make a good business plan. The total number of participants is 20 participants. In the preparation stage, the team of lecturers as resource persons for the community service program carried out a series of activities, including site surveys, licensing and socialization of the event concept. The next step is site preparation and preparation of training modules and supporting equipment and the next step is training implementation. To measure the success rate of this service activity, that is by looking at the youth who can make their own business plans. It is hoped that in the future the youth will be able to see business opportunities and become strong youths in business.